2015
DOI: 10.1159/000374051
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Eclampsia-Associated Reduction in Placental Growth Factor Impaired Beta Cell Proliferation Through PI3k Signalling

Abstract: Background/Aim: Reduction in serum placental growth factor (PLGF) frequently co-occurs with preeclampsia (PE) and gestational diabetes mellitus (GDM). Recently, we reported that impairment in gestational beta-cell mass growth may result from PE-associated reduction in PLGF and lead to development of GDM. Here, we studied the underlying mechanisms. Methods: We co-cultured primary mouse beta cells with mouse islet endothelial cells (MS1), with or without PLGF. We also cultured beta cells in conditioned media fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…Meanwhile, the invasion-promoting effect of PTP4A1 was also revealed in colorectal cancer [16], lung cancer [17] and HCC [19]. Third, we demonstrated that PTP4A1 promoted cell proliferation via PI3K/AKT signaling pathway and downstream molecules, such as GSK3β and CyclinD1, consistently with a recent report that activation of PI3K/AKT signaling in beta cells may promote beta-cell proliferation through increased cellular level of cell-cycle regulator CyclinD1 [26]. …”
Section: Discussionsupporting
confidence: 86%
“…Meanwhile, the invasion-promoting effect of PTP4A1 was also revealed in colorectal cancer [16], lung cancer [17] and HCC [19]. Third, we demonstrated that PTP4A1 promoted cell proliferation via PI3K/AKT signaling pathway and downstream molecules, such as GSK3β and CyclinD1, consistently with a recent report that activation of PI3K/AKT signaling in beta cells may promote beta-cell proliferation through increased cellular level of cell-cycle regulator CyclinD1 [26]. …”
Section: Discussionsupporting
confidence: 86%
“…Finally, gestational PLGF may stimulate endothelial cells within the pancreatic islets to release growth factors that activate the PI3K-AKT pathway ( Fig. 2 ), thus enhancing β-cell proliferation ( 73 ). A previous study demonstrated that Pref-1 independently facilitated the phosphorylation of AKT and ERK1/2, and triggered alterations in the expression of FOXO1 and Pdx1 ( Fig.…”
Section: Growth Factor Signaling Pathwaysmentioning
confidence: 99%
“…It has been estimated that 5%–7% of pregnancies worldwide are complicated by this disorder, resulting in a very large disease burden [1]. Although much research has been devoted toward this topic, its pathogenesis is still incompletely understood yet [2-5]. …”
Section: Introductionmentioning
confidence: 99%